Synthesis and characterization of heterogeneous mixed oxide catalysts based on egg shell for biodiesel production from waste cooking oil - Mansir, Nasar (2018)
Biodiesel is one of the most promising biofuel alternatives to conventional fossil fuel, considering its number of advantages particularly environmental benign and availability of feedstock. Conventionally, homogeneous catalytic system is used for the production of biodiesel in commercial scale using high grade feedstock such as soybean oil, palm oil and sunflower oil. However, the current biodiesel production process is no longer sustainable considering the high cost of feedstock and other environmental related issues associated to homogeneous catalyst system. Newly developed calcium oxide based catalysts doped with mixed bimetallic oxides were synthesized using simple wet impregnation method. The synthesized mixed oxide catalysts were used for the transesterification of waste cooking oil using normal reflux method to produce fatty acid methyl ester (FAME). The catalysts (Molybdenum Zirconia Calcium oxide (Mo-Zr/CaO), Manganese Zirconia Calcium oxide (Mn-Zr/CaO), Tungsten Zirconia Calcium oxide (W-Zr/CaO), and Tungsten Molybdenum Calcium oxide (W-Mo/CaO) were characterized to investigate their physico-chemical properties using various characterization techniques such as XRD, TPD, BET, SEM, EDX, TGA and FTIR. The basicity and acidity of the catalysts determined their activity towards transesterification reaction. The Mo-Zr/CaO and Mn-Zr/CaO catalysts achieved 90.1% and 92.1% FAME yield under the reaction temperature of 80 oC and reaction time of 3 h in both cases. W-Zr/CaO catalyst recorded biodiesel yield of 94.1% at 80 oC reaction temperature, & 1 h reaction time. W-Mo/CaO catalyst achieved the biodiesel yield of 96.2% at reaction temperature of 70 oC, & 2 h reaction time. The order of activity of the synthesized catalyst for FAME production is W-Mo/CaO > W-Zr/CaO > Mn-Zr/CaO > Mo-Zr/CaO. The Ca2+ leaching has reduced significantly with the increase in transition metal mixed oxide loading over the CaO surface. Additionally, all the synthesized catalysts could convert high FFA waste cooking oil to FAME at mild reaction conditions and be reused and regenerated for subsequent biodiesel production cycle. The most stable catalyst (W-Mo/CaO) achieved 90 % FAME yield at 70 oC temperature and 2 h reaction time in the 5th reusability cycle. The synthesized biodiesel was tested and met the biodiesel standard quality parameters according to ASTM D67751 and EN 14214.